P229 Factors affecting inhaler choice and adherence in urban Liverpool. (2nd December 2011) - Tack, G; Tjia-Leong, E; Davies, L; Warburton, C J
Abstract : Introduction: Salmeterol/Fluticasone propionate (SFC) in the form of a dry powder inhaler (DPI) is often used in COPD, however it is also available as a metered dose inhaler (MDI). This is unlicensed for COPD and costs considerably more. At our hospital, a high proportion of COPD patients used SFC MDI, the reasons for this were unclear. This study aimed to investigate the effects of patient preference on inhaler adherence. Methods: Patients admitted to hospital with an exacerbation of COPD taking either SFC DPI or MDI were recruited. All patients completed a pre-discharge questionnaire about their inhaler usage. MDI patients were switched to DPI, following education and check of their inspiratory flow. GPs were informed that their patient was involved in a study of inhalers but not the detail of the study. All patients underwent a further questionnaire at 3 months. Results: 101 patients, mean (SD) age was 69 (9) years and 50% male. On admission, 66 (65%) on MDI, 35 (35%) on DPI. 100% of MDI patients were switched to DPI. At 3 months, follow-up data were available on 81 patients. Of those patients admitted on DPI, 26/29 (92%) remained on it and were satisfied with it. In the group switched from MDI to DPI, 26/52 (50%) were again receiving MDI at 3 months. 16 patients had asked for their prescription to be changed back. 10 patients had their prescription changed without their knowledge or did not receive DPI on discharge. Regardless of the reasons for the switch, 18 patients stated they preferred MDI over DPI. Reasons why patients requested the change back to MDI included dry powder irritating the throat, dry mouth and the inhaled dose not going into the lungs. Conclusion: Following a relatively simple intervention 50% of COPD patients using SFC MDI could be switched and maintained on SFC DPI. Factors relating to a return to MDI included patient related and organisational factors. A whole system approach is required to effect robust systematic change in this patient group, however approximately a third of the group switched to DPI will still request a change back to MDI.